Trimming defective perovskite layer surfaces for high-performance solar cells - Kim, Chanhyeok; Kim, Kihoon; Kim, Youngmin; Tsvetkov, Nikolai; Jeon, Nam Joong; Kang, Bong Joo; Min, Hanul (Royal Society of Chemistry, 2024)
The defect density on the top surface of the perovskite thin film was significantly higher than that in the bulk due to dangling bonds and substantial strain. This excess strain led to a blue shift in the bandgap and increased non-radiative recombination, adversely affecting the performance of photovoltaic devices. We addressed this issue by selectively removing the defective top layer of the as-prepared perovskite using a controlled mixture of solvent and anti-solvent. By controlling the solvent-to-anti-solvent ratio, we were able to adjust the thickness of the layer removed without compromising the surface morphology and optical absorption properties. The modified perovskite thin film, with a 50 nm top layer removed, exhibited a reduced bandgap, enhanced carrier lifetime, and decreased strain and defect concentration. Perovskite solar cells derived from this refined top surface deliver a champion power conversion efficiency of 26.25% (certified efficiency of 25.5%). The defect density on the top surface of the perovskite thin film was significantly higher than that in the bulk. A trimming solvent treatment removed the defective top surface, substantially reducing the defect concentration and strain.